Analysis of Position Angle of Arrival in Multipath Fading Channel using Correlated Double Ring Channel Model for VANET Communications - Jans Hendry; Anggun Fitrian Isnawati; Wahyu Pamungkas (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Correlated Double Ring channel modeling in the mobile to mobile communication system (M2M) and vehicular based communication system was pointed out. This modeling required the transmitter and receiver were randomly moving and surrounded by scatterers in a static ring. The scatterers’ positions were placed randomly at the radius of the ring of transmitter and receiver. Received signals were measured based on complex envelope parameters. Two signals propagation scenarios were implemented, they were signals of Rayleigh and Rician distributed. In order to calculate the Rayleigh and Rician complex envelope values, there were some parameters involved which were Angle of Arrival (AoA) and velocity of transmitter and receiver that created Doppler effects. The effects of AoA parameter were investigated towards envelope complex values of Rayleigh and Rician according to predetermined various velocities and scatterers’ positions were divided into four positions criteria. The simulation result shows that for scheme 2 at velocity 40 m/s, distribution magnitude for Rayleigh is 0,1 and Rician is 0,5. It concludes that Rician distribution always outperforms Rayleigh distribution for all predetermined velocities and this scheme give the largest magnitude over all. This is because of the closest distance between scatterers of transmitter and receiver. Also, certain velocities range over all scatterers’ positions, the magnitude of Rayleigh and Rician complex envelope have similar graphic tendency.